Governmental Coordination between Wali Nanggroe and the Aceh Adat Council in the Preservation of Cultural Traditions in Aceh Province - Nurmalisa H Chawari; Irwan Tahir; Sri Hartati (Journal of Governance and Social Policy, 2026)
This study explores the institutional coordination between the Wali Nanggroe and the Aceh Adat Council (MAA) in preserving Acehnese culture within the framework of asymmetric decentralization. Using a qualitative approach through observation, in-depth interviews, documentation, and audiovisual materials, the data were analyzed inductively with thematic coding. The findings indicate that although both institutions possess strong legal foundations and sociocultural legitimacy, their coordination remains partial and fragmented. The Wali Nanggroe serves normatively as a symbolic unifier, while the MAA functions as the technical executor of adat governance. Major obstacles include overlapping authority, limited resources, and a tendency toward ceremonial rather than substantive collaboration. From a good governance perspective, coordination fulfills only some principles of participation, accountability, transparency, and effectiveness. The study concludes that strengthening coordination requires clearer role delineation, systematic evaluation, and adaptive strategies such as education, policy integration, and digital platforms to ensure that Acehnese cultural preservation remains relevant in the era of globalization.